Income Distributions in Two Experimental Economies - Battalio, Raymond C.; Kagel, John H.; Reynolds, Morgan O. (Journal of Political Economy, 1977)
Data on individual labor earnings are reported from two experimental economies where the primary factors responsible for income differences were differences in tastes for market income versus leisure and differences in abilities working manual job tasks. Measured income dispersion under these conditions was strikingly similar to that in the United states and other market economies, indicating that these two factors alone are sufficient to generate such income differences. Further, in tests of the functional form of the distributions of income, the hypothesis of lognormality fit better than the hypothesis of normality, just as it does in national data.